Effect of chickpea in production of chickpea biscuit / Nurilyani Mashuri - Mashuri, Nurilyani (2008)
The study was carried out to determine the suitable amount chickpea to be added in the biscuit formulations. The chickpea biscuit was prepared with addition of raw chickpea with different formulation that consist of 5%, 10%, 15% and 20% of chickpea. Basic formulation of biscuit was developed without addition of chickpea. Evaluation of colour of biscuit was measured by using Minolta colorimeter CR-300. The high amount of chickpea was found to be the best formulation and it was agreed with appearance attributes in sensory evaluation results. Determination of texture by using texture analyzer TAXT2i indicated that there were textural changes in biscuit baked with addition of chickpea in formulation. The results showed that the fracturability of biscuit increased as the proportion of chickpea in formulation was increased. It was found that biscuit baked analysis and sensory evaluation with different amount of chickpea results texture of chickpea biscuit positively correlated with texture of sensory evaluation. The findings in this study revealed that, biscuit with the addition of chickpea was acceptable. This type of biscuit will increase the usage of chickpea and also could provide biscuit with high nutritional value